2018
DOI: 10.1215/23290048-7257028
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution and Change in Tang Poetry: Data Analysis from the “Chronological Map of Tang-Song Literature”

Abstract: This article uses data to analyze the geographic distribution and transformation of the poetic world in the Tang dynasty (618–907 CE). There are two ways we can examine spatial distribution and movement in Tang poetry. The first is a static examination of poets' hometowns (jiguan 籍貫). This method looks at the distribution of poets during a specific period to understand where greater or lesser numbers of poets were born, which places could be considered the center of Tang poetry, and what kinds of geographical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Therefore, when describing the characteristic information of poets' names, in addition to their names, style names, and pseudonyms, they should also include aliases that often appear in their poems. When describing the characteristics of gender, birth, and regional attributes, it is necessary to not only describe the birthplace of the poet but also describe the space-time track of the poets according to the chronological map of Tang and Song literature constructed by Wang Zhaopeng [29]. In addition, according to the development stage of Tang poetry, we should supplement the ages attribute.…”
Section: Authorship Attribution Componentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when describing the characteristic information of poets' names, in addition to their names, style names, and pseudonyms, they should also include aliases that often appear in their poems. When describing the characteristics of gender, birth, and regional attributes, it is necessary to not only describe the birthplace of the poet but also describe the space-time track of the poets according to the chronological map of Tang and Song literature constructed by Wang Zhaopeng [29]. In addition, according to the development stage of Tang poetry, we should supplement the ages attribute.…”
Section: Authorship Attribution Componentmentioning
confidence: 99%
“…As shown in Figure 7, poets who have a citation relationship with Li Bai (李白) include Du Fu (杜甫), Gao Shi (高适), and He Zhizhang (贺知章). Via the chronological map of Tang and Song literature constructed by Wang Zhaopeng [29], it can be observed that although Li Bai was born thousands of miles away, most areas dominated by the Tang Dynasty were covered with his footprints.…”
Section: Authorship Attribution (Aa) Componentmentioning
confidence: 99%